y^2-xy+x^2=7
2y dy/dx - x(dy/dx) - y(dx/dx) + 2x (dx/dx) = 0 , remember dx/dx = 1
simplify and solve for dy/dx
show me your steps so I can check your work.
Find dy/dx for implicit differentiation
y^2-xy+x^2=7
3 answers
2y-x (dy/dx)-y(dy/dx)+2x=0
subtract -2y +x and move over to the right side replacing zero
It becomes: -y+2x(dy/dx) = -2y dy/dx + x
Divide both sides by by -2y+x
Answer= 2x-y/ x-2y
subtract -2y +x and move over to the right side replacing zero
It becomes: -y+2x(dy/dx) = -2y dy/dx + x
Divide both sides by by -2y+x
Answer= 2x-y/ x-2y
I agree IF you place brackets like this ....
(2x-y)/ (x-2y)
(2x-y)/ (x-2y)